Determination of ethyl glucuronide and fatty acid ethyl esters in hair samples. (6th November 2016) - Oppolzer, David; Barroso, Mário; Passarinha, Luís; Gallardo, Eugenia
Abstract: Hair testing for alcohol biomarkers is an important tool for monitoring alcohol consumption. We propose two methods for assessing alcohol exposure through combined analysis of ethyl glucuronide (EtG) and fatty acid ethyl esters (FAEEs) species (ethyl myristate, palmitate, stearate and oleate) in hair (30 mg). EtG was analysed by liquid chromatography–tandem mass spectrometry, while FAEEs were analysed by gas chromatography–tandem mass spectrometry using electron impact ionization. Both methods were validated according to internationally accepted guidelines. Linearity was proven between 3 and 500 pg/mg for EtG and 30–5000 pg/mg for FAEEs, and the limits of quantification were 3 pg/mg for EtG and 30 pg/mg for each of the four FAEEs. Precision and accuracy were considered adequate, processed EtG samples were found to be stable for up to 96 h left in the injector and processed FAEEs samples for up to 24 h. Matrix effects were not significant. Both methods were applied to the analysis of 15 authentic samples, using the cut‐off values proposed by the Society of Hair Testing for interpretation. The results agreed well with the self‐reported alcohol consumption in most cases, and demonstrated the suitability of the methods to be applied in routine analysis of alcohol biomarkers, allowing monitoring consumption using low sample amounts.